2017
DOI: 10.1177/0018726716682308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an organizational health intervention for low-skilled workers and immigrants

Abstract: We conducted this realist evaluation study of an organizational health intervention involving 421 low-skilled workers (50% female), half of whom were immigrants, in three companies over six months. Non-profit agencies implemented peer-mentoring and taught peer-mentors and line managers how to enhance social support in order to improve workers’ work situation in a participative way. We formulated five mechanisms of change: the company management encouragement mechanism, the role model mechanism, the peer-mentor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 70 publications
3
56
1
Order By: Relevance
“…It is likely that a careful investigation, like the one we report on in our study, would reveal similar problems in these two studies. Perhaps, by comparison, the Busch et al (2017) and Van Gils et al (2018) studies composed of much more diverse and heterogeneous samples than ours, could face even much greater problems than our study of junior professionals in a consultancy, representing a Western, well-educated, homogenous group with excellent skills in English.…”
Section: Discussioncontrasting
confidence: 61%
“…It is likely that a careful investigation, like the one we report on in our study, would reveal similar problems in these two studies. Perhaps, by comparison, the Busch et al (2017) and Van Gils et al (2018) studies composed of much more diverse and heterogeneous samples than ours, could face even much greater problems than our study of junior professionals in a consultancy, representing a Western, well-educated, homogenous group with excellent skills in English.…”
Section: Discussioncontrasting
confidence: 61%
“…Studies involving autonomy-supportive training have evaluated the effect ranging from 2 weeks, 2 months to a year (Aelterman, Vansteenkiste, Van Keer, & Haerens, 2016;Lewis et al, 2016). However, evaluation beyond 3 months is not recommended for studies involving employees in low-skilled occupations, due to high attrition risk (Busch, Koch, Clasen, Winkler, & Vowinkel, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has confirmed the important contributions of the work organization to worker safety, health, and wellbeing [2,11,19,21,24,55]. We relied on four underlying essential elements in the organizational change process [56].…”
Section: Methodsmentioning
confidence: 99%
“…Women, young workers, those with low levels of education, and immigrants are overrepresented in these jobs [4,7,8,9,10]. These positions are often characterized by job insecurity; uncertainty around work hours, contributing to instability in earnings; significant physical work demands; repetitive work; and low job decision latitude and autonomy [11,12,13,14]. Many low-wage workers are employed by contracting agencies or firms that then contract out specific services to “host” employers, thereby creating multiple layers of responsibility for workplace policies and working conditions [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation